(untitled) (Research, Society and Development, 2023)
The human being goes through several changes that include the aspects of the phases of life, senescence is seen as the last phase to be experienced. In this scenario, about sexuality related to aging, it is evident the occurrence of myths and stereotypes that can compromise the safety of sexual practice in this age group. The aim was to know the perception of the elderly in relation to sexual life in old age and sexually transmitted infections. This is an integrative literature review, in the databases: SciELO, LILACS, BDENF and MEDLINE, using Boolean operators in conjunction with the descriptors of health (DeSC) in the following combinations: "Sexual life" AND "Elderly" AND "Sexually Transmitted Infections", in English and Portuguese languages, which sought articles published between 2016 and 2022. The sample was made up of 10 articles. Through the results, it was possible to highlight that the studied population showed a high percentage of active maintenance of sexual practice, low adherence to condom use in a context in which they have more than one partner, followed by the feeling of not considering themselves vulnerable to STIs. Thus, it was concluded that the elderly are exposed by the little perception that sexual life in old age, although it is no longer related to reproductive life, makes them more susceptible to STIs by not using barrier methods. In this scenario, it is necessary to clarify the doubts that contribute to the deconstruction of myths and prejudices that surround this public so that the practices of sexual activity do not generate greater risks for this population.